Following micelles with rheo-NMR - Almeida, Pedro L. (2020)
The rheological behaviour of the micellar system Cetyltrimethylammonium Bromide (CTAB)/Sodium Salicylate (NaSal) in water is highly dependent on the components concentration and temperature. The surfactant CTAB forms spherical micelles in water above a certain concentration (CD), which upon addition of a salt (NaSal) elongate to form entangled wormlike structures, also known as “living polymers”. The viscosity of wormlike micelles solutions increases dramatically with the increase of salt concentration (CS), changing from quasi-newtonian to a viscoelastic behaviour in the gel-like, highly entangled state. Such rich rheological behaviour has already been characterized by some of the authors and in the literature, e.g., [1-3]. The rheological behaviour of CTAB/NaSal aqueous solutions in the regime CD/Cs>1 are presented in this work. Furthermore, we followed the rheological behaviour of these solutions by a rheo-NMR technique, allowing for an insight of “what happens” inside the sample during the application of a shear flow. To achieve this goal we performed quantitative flow rate measurements using velocity NMR mapping in the rheo-NMR experiments, developed by Callaghan [4]. Attempts to characterize the velocity profile in this system has already been described [5] using an optical-shear flow experimental setup, although for solutions with CD/Cs<1, where the surfactant [CTAB] has always a smaller concentration than the salt [NaSal].